2004
DOI: 10.1002/pssa.200409045
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube/magnesium composites

Abstract: Novel magnesium matrix composites reinforced with carbon nanotubes have been processed by powder metallurgy. Blends of metal powders and multi-wall carbon nanotubes were compacted by uniaxial hot pressing followed by hot isostatic pressing. A uniform dispersion of nanotubes in the metal matrix was obtained. A coating method of nanotubes is described, which is promising to improve the matrixreinforcement bonding strength. R54 E. Carreño-Morelli et al.: Carbon nanotube/magnesium composites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 7 publications
1
46
0
Order By: Relevance
“…Previous studies indicated characteristics of the metal matrix composites (MMCs) reinforced with CNTs, where industrial metals such as aluminum, magnesium, nickel, copper and their alloys were used [5][6][7][8][9][10][11][12][13][14]. Titanium (Ti) and titanium alloy are also interested as the matrix material because they are widely used in various industrial applications, for example, automotive, motorcycles, and airplane industries due to their high specific strength and Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated characteristics of the metal matrix composites (MMCs) reinforced with CNTs, where industrial metals such as aluminum, magnesium, nickel, copper and their alloys were used [5][6][7][8][9][10][11][12][13][14]. Titanium (Ti) and titanium alloy are also interested as the matrix material because they are widely used in various industrial applications, for example, automotive, motorcycles, and airplane industries due to their high specific strength and Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several significant studies showed that the introduction of carbon nanotubes resulted in lightweight composites with enhanced mechanical strength. [7][8][9][10][11] In particular, we proved that the short, linear and well-ordered MWNTs directly contributed to 25 and 11 % increases in the elastic modulus and tensile strength of magnesium alloy composites, respectively. 11 From these results, we envisage that MWNTs-filled magnesium composites are possibly the best candidates for constructing lightweight materials for automobiles, always considering an energy-efficient environment.…”
mentioning
confidence: 61%
“…NiCrAl 67% 22% 11% on the fact that temperature was of great influence and important than the current during sintering process [20][21][22][23].…”
Section: Ni Cr Almentioning
confidence: 99%